Arabic traditional school in Cameroon and Arabic language - Ibrahim, Mo'men (Journal of Humanities & Social Sciences, 2018)
North Cameroon is the scene of the Islamic presence in the country, thanks to its membership in the State of Kanem, Then to a territory belonging to the State of Sheikh Usman Ben Fodio in Nigeria. This historical advantage has made the region a natural starting point for arab education in the country. ‘’The Traditional Arabic School’’ wich is the subject of this study, was the first institution to have provided Arabic language education in Cameroon. This was so respected by the muslim community of the country. It was the only light that was responsible for popularizing Arabic language and culture for many decades. Before addressing the fundamental questions of this study, the researcher briefly mentioned the ethnic groups considered as the main actors for the popularization, its historical roots and the ways by which this Arabic language has arrived in the country. In addressing the history and impact of the ‘’Traditional Arabic School’’ on arabic language popularization in the country, he briefly mentioned its history, starting with modern school. Although it arrived relatively late, the modern school is currently taking the lead in spreading the Arabic language in the country. Furthermore, the researcher addresses the threatening issues of the ‘’Traditional Arabic School’’ such as the curriculum, pedagogy and textbook used in this school that will, no doubt, have negative impacts on educational results. ‘’The Traditional Arabic School’’, with its importance in the dissemination of the Arabic language and its predominance in this area, continues to be threatened with extinction by these problems which will be the subject of discussion during this study.